Clinical pharmacokinetics and pharmacodynamics of venetoclax, a selective B‐cell lymphoma‐2 inhibitor - Ahmed Hamed Salem; Rajeev M. Menon (Wiley, 2024)
Abstract Venetoclax, a highly potent BCL‐2 inhibitor, is indicated for treatment of some hematologic malignancies as monotherapy, and/or in combination with other agents. Venetoclax pharmacokinetics has been extensively characterized in patients and healthy participants. After oral dosing, the median time to reach maximum plasma concentration ranged from 5 to 8 h and harmonic mean half‐life ranged from 14 to 18 h. Food increases venetoclax bioavailability by 3-5‐fold and venetoclax should be administered with food to ensure adequate and consistent bioavailability. Venetoclax is eliminated via cytochrome P450 (CYP)3A metabolism, and a negligible amount of unchanged drug is excreted in urine. Strong CYP3A/P‐glycoprotein inhibitors increased venetoclax exposures (AUC) by 1.44‐ to 6.90‐fold while a significant decrease (71%) has been observed when dosed with strong CYP3 inducers. Venetoclax does not inhibit or induce CYP enzymes or transporters. Venetoclax pharmacokinetics is not appreciably altered by age, weight, sex, but the exposure is up to twofold higher in participants from Asian countries. Mild‐to‐severe renal impairment or end‐stage renal disease do not alter venetoclax exposures, and venetoclax is not cleared by dialysis. Although mild‐to‐moderate hepatic impairment does not affect venetoclax exposures, twofold higher exposure was observed in subjects with severe hepatic impairment. Venetoclax exposure is comparable across patients with different hematologic malignancies and healthy participants. Overall, venetoclax exposure is only affected by food and CYP3A modulators and is only higher in Asian subjects and subjects with severe hepatic impairment. Venetoclax exposure-response relationships are malignancy‐dependent and can be different between monotherapy and combination therapy.